(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2021)
The purpose of this work is to demonstrate that the material on which palaeo-Hispanic script was written was usually made of organic elements. While inscriptions represent but a minor part of the written production, they constitute the sole instances that could possibly be preserved because of the non-organic material used, i.e. stone and metal. The bulk of the written production from these ancient societies has inevitably disappeared yet the presence of implements such as cretulae, styluses and inkwells indicates that materials such as papyrus and wax tablets were habitually used for writing.